Kandungan Nitrat, Fosfat, dan Silikat di Perairan Pantai Pandawa, Bali - Jeniarti, Mila; Perwira, Ima Yudha; Negara, I Ketut Wija (Current Trends in Aquatic Science, 2022)
This study aimed to measure the concentration of nitrate, phosphate, and silicate in the water of Pandawa Beach waters. This study was conducted at the Kutuh Village (Badung, Bali, Indonesia), from December 2019 to January 2020. The water sample was collected from the location every week for one month. The water sample was taken from the surface, middle, and bottom of the water. Measurement of nitrate and silicate was performed using Salifert KIT Nitrate and Silicate, while measurement of phosphate was performed using Hanna 713 KIT analysis. The result showed that concentration of nitrate in the Pandawa Beach Waters was ranging from 0,91 to 2,00 mg/L. Concentration of phosphate was ranging from 0,32 to 1,93 mg/L, while silicate was ranging from 0,07 to 0,52 mg/L.